Evaluating the Role of Entrepreneurial Self-Efficacy on Entrepreneurial Intention of Tehran University (Case Study of Engineering Campus) - Khodabakhshi, Sara (Journal of Education and Vocational Research, 2012)
Entrepreneurship is the engine of economics of human society. In most countries, entrepreneurship, and especially start up of new businesses is most essential matter. Intention to run business is the base of entrepreneurial action. People, who have entrepreneurial intention, expect to start businesses in the future. In this study, we evaluated the impact of entrepreneurial self-efficacy on entrepreneurial intention. Women entrepreneurship is very important economic matter. Today, many of developed and developing countries, focus on the importance of women entrepreneurship and the enterprises founded by them (GEM, 2010). In this study, we implemented two modified questionnaire: first; Shapero’s entrepreneurial intention questionnaire (Shapero, 1982) and Entrepreneurial self-efficacy questionnaire (DeNoble, et al., 1999). In order to analyze gathered data, we used SPSS11 Software, regression and Coefficient. Result shows that entrepreneurial self-efficacy has positive effect on entrepreneurial intention.